THE REAL JANE AUSTEN: AUSTEN’S SHIFTING IMAGE - Simionato, Deborah Mondadori (2018)
ABSTRACTJane Austen is one of the most important and wildly known authors in the English language. Despite her unrelenting fame, very little is known about the actual woman who lived from 1775 to 1816 – her family insisted she led a quiet life and they burned her presumably most compromising letters. Readers and scholars were left with an unfinished sketch by Austen’s sister, Cassandra, later modified to fit the Victorian expectations of what a proper lady ought to be. In 2011, a new portrait has been found, one of a mature and independent authoress. This article aims to look at Austen’s life in order to glimpse at the woman behind the images, understanding how Austen’s image changed alongside her readers.Key words: Jane Austen, portraits, biography, English Literature.